Physical Activity And Intermittent Fasting Interventions To Improve The Physical Fitness Of Physical Education Teachers - Finsensius Mbabho; Angga Indra Kusuma (LPPM Universitas PGRI Adi Buana Surabaya, 2024)
This study aims to examine the impact of physical activity and intermittent fasting interventions on the physical fitness of teachers. An experimental method with a pretest-posttest design was employed, involving 50 teachers aged 26-35 as the sample. The physical activity and intermittent fasting interventions were applied over 6 weeks, with physical fitness measured using the Beep Test to assess VO2 Max and heart rate monitoring via a smartwatch. The results indicate a significant effect of physical activity and intermittent fasting interventions on improving teachers' physical fitness, reflected in increased VO2 Max scores and heart rate stability. This study provides valuable insights into how healthy lifestyle interventions can enhance physical fitness for educators, particularly in the productive age group.